Assay data of spent nuclear fuel: the lab-work behind the numbers - Van Winckel, Stefaan; Alvarez-Sarandes, Rafael; Serrano Purroy, Daniel; Aldave de las Heras, Laura (Frontiers in Energy Research, 2023)
Computational modelling for spent nuclear fuel (SNF) characterization is already widely used and continuously further developed for a plethora of safety related applications and licensing issues in SNF management. An essential step in the development of these methodologies is the validation: the demonstration that the SNF elemental and isotopic composition is sufficiently accurately predicted by the code calculations. This validation step requires experimentally measured nuclide concentrations in SNF, together with an estimation of related uncertainties. The SFCOMPO 2.0 database of OECD/NEA 1 is a database of such publicly available assay data of SNF.A basic understanding of all analytical steps that finally result in assay data of SNF is important for modellers when assessing the 'fit-for-validation' requirement of an experimental dataset. The aim of this article is to explain users of such datasets the complex analytical pathway towards assay data. Points of attention, challenges and pitfalls all along the analytical pathway will be discussed, from sampling, dissolution procedures, necessary dilutions and separations, available analytical techniques, some related uncertainties, up to reporting of the results.